(untitled) (Kinesiology, 2022)
Given the importance of physical activity for the prevention of overweight, this study sought to determine the type and number of physical activity risk behaviours that were associated with overweight in Croatian school children and their association with maternal characteristics – mothers’ formal education, employment, and weight status. This paper used data from the Croatian Childhood Obesity Surveillance Initiative study from 2015/2016. During an eight-week period, anthropometric measurements of children were taken. Data on children’s physical activity risk behaviours and their mothers’ characteristics were provided by the mothers of 4,045 children from the second and third grade (median age 8.6 years) who were included in the analysis. Insufficient active play outdoors, excessive screen time and exhibiting two or three physical activity risk behaviours were significantly associated with childhood overweight. Children of less educated mothers had lower odds for insufficient active play outdoor and higher odds for insufficient frequenting of a sports or dancing club and exhibiting one, two or three physical activity risk behaviours. Children of mothers who were overweight had higher odds for insufficient sleeping, insufficient frequenting of a sports or dancing club and exhibiting two risk behaviours. Children of unemployed mothers had higher odds for insufficient frequenting of a sports or dancing club and for exhibiting two or three risk behaviours. Physical activity risk behaviours in school children were associated with overweight, as well as mother’s characteristics. This finding should be taken into consideration when planning and implementing health promotion and childhood overweight prevention activities. Key words: sport, formal education, employment, weight status, risk behaviours, children